Loss Reduction in Port Harcourt 33/11kv Distribution Networks By Power Factor Correction - Eseosa, Omorogiuwa; Mik, Kesiena (International Research Journal of Management, IT & Social Sciences, 2015)
Poor power factor often result to high losses of active power in the network. It measures the percentage of apparent power that can be used to do actual work by the loads. However, this result in reduction of systems reliability and creates safety problems and a much increased energy cost. These inductive loads include induction motors, transformers, and reactors and they have negative effect on the actual power used up by the loads. In this paper, Power factor correction (PFC) has been done by the addition of the needed capacitance to counteract the inductive load which is present in the electrical network of Port Harcourt distribution system. The load values, MVAr values and the existing power factor of Port Harcourt electricity network where used to derive the needed shunt capacitance to a most appropriate value of 0.95. This enabled current savings of 23.15 percent in all the 11kV buses as well as reducing the required MVA needed to feed the loads to 101.48MVA as against 132.07MVA when the power factor was 0.73. These reductions were achieved by adding a capacitance of 34.48MVAr and the current reductions reduce losses along the lines since the square of current is proportional to losses. Also the added system capacity will mean that more loads can be fed by the system when the added capacitance brings the system to a power factor of 0.95.Â